ChemInform Abstract: Peroxide Coordination of Tellurium in Aqueous Solutions. Issue 19 (April 2016) - Mikhaylov, Alexey A.; Medvedev, Alexander G.; Churakov, Andrei V.; Grishanov, Dmitry A.; Prikhodchenko, Petr V.; Lev, Ovadia
Abstract: The peroxo compounds (NH4 )4 Te2 (μ‐OO)2 (μ‐O)O4 (OH)2 (I) and (NH4 )5 Te2 (μ‐OO)2 (μ‐O)O5 (OH)·1.28H2 O·0.72H2 O2 (II) are isolated from aq.